BANK FAILURE IN INDONESIA: AN ANALYSIS OF THE CENTURY BANK CASE AND THE POTENTIAL OF ISLAMIC BANKING - Kusnan Kusnan (Taksasila Edukasi Insani, 2025)
The inherently risky nature of banking necessitates robust risk management practices. While banks implement risk management frameworks encompassing policies, procedures, and defined limits aligned with established risk management principles across all activities, bank failures, nonetheless, continue to occur. This paper investigates the factors contributing to bank failures in Indonesia, using the prominent case of Bank Century (2008) as a focal point. Through an in-depth analysis of Bank Century's financial performance, management and operations, and legal and compliance adherence, this study aims to identify key vulnerabilities. Furthermore, it explores, from a theoretical perspective, the potential of Islamic/Sharia banking principles to offer mitigating solutions and prevent similar occurrences.Keywords : Bank Failures, Financial Performance, Macro Economic, Risk Management, Islamic Bank